PEDAGOGICAL FEATURES OF FORMATION OF PROFESSIONAL COMPETENCE IN STUDENTS - Mamanazarov Uchqun Burxon o‘g‘li; Mirsagatova Nargiza Sayfullayevna (Research Focus International Scientific Journal, 2024)
This paper examines the pedagogical features of developing professional competence in students, which is vital for their successful transition into the workforce. As educational systems shift towards more competency-based models, understanding the methodology for nurturing key skills and knowledge in students has gained significance. This study explores various educational approaches, learning environments, and teaching strategies that facilitate the formation of professional competence. Drawing from theoretical frameworks and practical case studies, it highlights the essential components that educators must focus on to foster competence. The results show that integrating active learning, practical experience, and feedback mechanisms within the curriculum significantly enhances student competence.